The more things change, the more they stay the same: promises of bioeconomy and the economy of promises - Eversberg, Dennis; Koch, Philip; Lehmann, Rosa; Saltelli, Andrea; Ramcilovic-Suominen, Sabaheta; Kovacic, Zora (Springer Science and Business Media LLC, 2023)
This editorial lays out the core themes of the special feature and provides an overview of the contributions. It introduces the main argument, namely that the promises of far-reaching change made by recent bioeconomy policies are in fact strategically directed at avoiding transformative change to existing societal arrangements. Bioeconomy discourse showcases technological solutions purported to solve sustainability ‘problems’ while sustaining economic growth, but avoids issues of scalability, integration or negative consequences. Thus, bioeconomy policies, and particularly the latest versions of the predominantly European ‘bio-resource’ variety that have rhetorically integrated a lot of previous sustainability-minded criticism, serve to ward off or delay challenges to an unsustainable status quo, in effect prolongating the escalatory imperatives of capitalist modernity that are at the root of current crises. The editorial’s second part highlights the contributions that the 13 featured articles, based on theoretical considerations as well as policy analyses and empirical case studies from a range of countries, make to this argu